Sustainable and commercial development of aquaponics through the certification in Europe - Dos Santos, Maria José Palma Lampreia (2020)
Aquaponics is nowadays a sustainable practice of producing food with a short supply chain and with a very interesting need for development towards the sustainable production of foods. The main aim of this paper is to analyses the present situation of aquaponics in terms of commercial development and to define the main strategies to be overcome in order to promote its development. The methodology used is a systematic literature review based on the recent indexed references. The main results outline confirm besides aquaponics presents many benefits in terms of social, economic and environmental, therefore, so, its development must involve all the stakeholders from research to public decision-makers and consumers.